Inculcating Honesty Values in Boarding School: Study in Muhammadiyah Boarding School Yogyakarta - Sudrajat Sudrajat; Agustina Tri Wijayanti; Gautam Kumar Jha (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explored the incorporation of honesty values and associated challenges at a junior high school in Yogyakarta, employing qualitative methods with 13 participants, including principals, teachers, employees, and students. Using interviews, observations, and documentation for data collection and employing the Miles Huberman model for analysis, the research highlighted a holistic approach in instilling honesty through life skills education in academic and extracurricular activities, with teachers playing a pivotal role by example. It identified the main challenge as insufficient teacher numbers impacting effective supervision. The recommendation is for schools to adopt comprehensive strategies to promote honesty, fostering an environment conducive to developing student integrity.